Pengembangan Media Scrabble Dalam Pembelajaran Bahasa Arab Pada Siswa Kelas VA MI Ismaria Al-Qur’aniyyah Bandar Lampung - Faizatul Aulia, Paliya; Anwar, Khairil; Singgih, Muhammad (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
The aim of this research is to determine the design of the Scrabble media that will be used, to determine the feasibility of the Scrabble media and also to determine the effectiveness of the media that has been developed. The questions in this research include "What is the feasibility and effectiveness of the Scrabble media that has been developed?". This research is Research and Development (RnD) research and the development model that researchers use is ADDIE. The subjects in this research were 38 students of the VA MI Ismaria Al-Qur'aniyyah Bandar Lampung class. The results of this research show that this scrabble media has criteria that are suitable for use based on an assessment from material experts of 94% and media experts of 97%. Based on the results of calculations in the pre-test and post-test, it was found that the average was 26.31579 and 78.68421, which was an increase after using the Scrabble media. And also based on the results the significance value obtained is 0.000, where 0.000<0.05 can be interpreted as Ho being rejected and Ha being accepted. So the conclusion obtained in this research is that there is effectiveness of the Scrabble media in learning Arabic for class V students at MI Ismaria Al-Qur'aniyyah Bandar Lampung.